Manajerial Kepala Desa Taman Martani DIY dan Sukaraja Bandar Lampung dalam Musyawarah Perencanaan Pembangunan (Musrenbang) Desa - Ray Septianis Kartika (Research and Development Agency Ministry of Home Affairs, 2018)
The village head is a strategic policy-making actor in the administration of village governance. Starting from motivating the community to participate in the village musrenbang, accommodating the priority scale of village needs and creating a democratic and successful village musrenbang in the concept of development planning. This paper is one of the references that can provide information to the public in general related to the competence of the village head, especially in leading the musrenbangdes process. The competence of the village head is seen from the technical competence, conceptual competence and human competence held by the village head. This study uses qualitative methods presented descriptively. Data collection techniques are carried out by observation to the place where the village musrenbang takes place in the village hall, deepening of information through primary data obtained from the Village Head, BPD, and the village community. Secondary data was obtained by observing the village musrenbang process, the committee TE SK, the APBDes Accountability Report, the Proposed Village Musrenbang Priority. The results of the study found that the village heads in Sukaraja did not have technical capabilities such as discussing and revising the RKPDes draft, conceptual capabilities such as the lack of RPJMDes review team, budget planning and human capability analysis team such as the absence of village cadre formation process. Therefore the managerial to the village in musrenbangdes not only as a leader position but rather as a subject that is able to create a conducive climate during musrenbangdes take place.